The Determinants of Profitability in Banking and Its Implication for Risk Management: Evidence from UK Bank over 2003-2012 - Pan, Zijun (2013)
An unbalanced panel data set from Britain banks was applied to investigate the internal and external factors affecting profit in the banking industry over the period from 2003 to 2012 . This study is aimed to investigate the potential determinants of profit in the banking industry in the UK, and try to find out the relationship between bank profitability and its significant determinants. Also, this paper will combine the potential important and significant determinants with risk management framework, in order to find out the way which can improve the competition capacity in such a large competition banking market. It is found that liquidity and credit is the most important and significant factors in internal determinants for banking profitability (ROAA, ROAE and NIM). However, external determinants, including inflation rate, real interest rate and GDP, were found to be not very important to the profit in banks, except for GDP. A further discussion based on a lesson from the 2008 financial crisis will focus on the importance of managing and controlling the risks faced by banks, particularly in liquidity risk and credit risk.